POLA PEMBELAJARAN SEKOLAH MINGGU BUDDHA DI WIHARA DHAMMA PAÑÑA TEMANGGUNG - Rusmiyati, Rusmiyati; Setyaningsih, Setyaningsih; Parsiyono, Parsiyono (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
Learning plays an important role for one's success in achieving change, and this relates to how teachers teach. The way teachers carry on the duty which does not involve variations in the use of methods will affect students’ achievemen. The purpose of this study is to know the pattern of Buddhist Sunday School learning in the Dhamma Pañña Monastery Krajan Kalimanggis Kaloran Temanggung. This research uses qualitative methods of descriptive. The subject of this studies are the heads of the monasteries, mentor teachers, parents, and students. The object used is a learning pattern. The data collection techniques used are interviews, observations, and documentation. Validity of data obtained through continuous observation, triangulation, and member check. Data analysis techniques using Milles and Huberman methods which include data collection (data collection), data reduction, data presentation (display data), and drawing conclusions or conclusion drawing verification. Based on the results of the study, it can be found as follows: (a) The learning pattern used by teachers is the learning pattern and media to achieve the purpose, the selection of the content and methods, teachers, media and students; (b) The role of a mentor teacher in a Sunday school activity as mentors (the teacher as a model that gives examples of real action such as Namaskara), as educators (teachers provide a level of freedom to the students when the teacher provides assignment, and when students have not completed it, they can not play among themselves), the facilitator (teachers conditioned student-centered learning), motivators (teachers assess the outcome of students' work); (c) The impact of Sunday school activities on the cognitive realm (the students’ recall increases), affective (emerging work attitudes, patience, and confidence), psychomotor (increasing creativity in terms of drawing, coloring, and making flowers shape from folding paper.